Seismic airgun sound propagation in shallow water of the East Siberian shelf and its prediction with the measured source signature - Han, Dong-Gyun; Kim, Sookwan; Landrø, Martin; Son, Wuju; Lee, Dae Hyeok; Yoon, Young Geul; Choi, Jee Woong; Yang, Eun Jin; Choi, Yeonjin; Jin, Young Keun; Hong, Jong Kuk; Kang, Sung-Ho; et al. (Frontiers in Marine Science, 2023)
Seismic airgun sound was measured with an autonomous passive acoustic recorder as a function of distance from 18.6 to 164.2 km in shallow water (<70 m) at the continental shelf of the East Siberian Sea in September 2019. The least-square regression curves were derived in the zero-to-peak sound pressure level, sound exposure level, and band level in a frequency range between 10 and 300 Hz using the initial amplitude scaled from the near-field hydrophone data. In addition, propagation modeling based on the parabolic equation with the measured source spectrum was performed for range-dependent bathymetry, and the results were compared with the band level of the measurements. The sediment structure of the measurement area was a thin layer of iceberg-scoured postglacial mud overlying a fast bottom with high density based on grounding events of past ice masses. The observed precursor arrivals, modal dispersion, and rapid decrease in spectrum level at low frequencies can be explained by the condition of the high-velocity sediment. Our results can be applied to studies on the inversion of ocean boundary conditions and measurement geometry and basic data for noise impact assessment.